2011
DOI: 10.1130/g111a.1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Earth’s eroding surface with 10Be

Abstract: For more than a century, geologists have sought to measure the distribution of erosion rates on Earth's dynamic surface. Since the mid-1980s, measurements of in situ 10 Be, a cosmogenic radionuclide, have been used to estimate outcrop and basin-scale erosion rates at 87 sites around the world. Here, we compile, normalize, and compare published 10 Be erosion rate data (n = 1599) in order to understand how, on a global scale, geologic erosion rates integrated over 10 3 to 10 6 years vary between climate zones, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
477
8
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 490 publications
(532 citation statements)
references
References 53 publications
(63 reference statements)
45
477
8
2
Order By: Relevance
“…S5), evidently because exposed bedrock weathers slower than bedrock covered by soil in the Sierra Nevada (19,48). Previous cosmogenic nuclide studies of other granitic landscapes (e.g., 47) have shown that this is common (Fig. 4).…”
Section: Implications For Landscape Evolutionmentioning
confidence: 90%
See 1 more Smart Citation
“…S5), evidently because exposed bedrock weathers slower than bedrock covered by soil in the Sierra Nevada (19,48). Previous cosmogenic nuclide studies of other granitic landscapes (e.g., 47) have shown that this is common (Fig. 4).…”
Section: Implications For Landscape Evolutionmentioning
confidence: 90%
“…A global compilation of cosmogenic nuclide data (gray, after ref. 47) demonstrates that erosion from soil-mantled granitic terrain (Bottom; n = 416) is typically faster than it is from exposed granitic bedrock (Top; n = 250). This is consistent with cosmogenic nuclides in samples from the Sierra Nevada study region (black, with labeled averages ± SEM and number of samples); erosion is more than two times faster on average in soil-mantled terrain (Bottom) than it is in bare rock (Top).…”
Section: Methodsmentioning
confidence: 99%
“…For possible values of C o , (0.001-10 mm/y; ref. 35), Z b will be above the elevation of an adjacent channel for K=∅ between ∼10 −13 and 10 −8 m/s (Fig. S4).…”
Section: Model For a Bottom-up Limit To Bedrock Weatheringmentioning
confidence: 99%
“…If these rock-surface-lowering values from the Esperanza Fire are assumed to represent a typical fire effect and are multiplied by 20 fires per 1000 yr (fire recurrence interval of 50 yr), then the rock erosion rate would range from 14 to 246 mm/k.yr. The high end of this range exceeds reported erosion rates based on 10 Be concentration in bedrock surfaces (e.g., Portenga et al 2011) and does not seem to be a reasonable sustainable rate for this landscape. Our next consideration is whether the Esperanza Fire might be considered a typical chaparral wildfire.…”
Section: Discussionmentioning
confidence: 39%